2015
DOI: 10.3892/mmr.2015.3631
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of the GCK gene body is associated with the risk of essential hypertension

Abstract: Abstract. Essential hypertension (EH) is commonlyaccompanied by a dysfunction of glucose metabolism. Glucokinase (GCK) is a key enzyme involved in glucose metabolism. The aim of the present study was to investigate whether GCK gene-body methylation contributed to the risk of EH. A total of 47 patients with EH and 47 age-matched controls were recruited for methylation research in the current study. GCK gene-body methylation was measured using bisulphite pyrosequencing technology. DNA methylation levels were clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In previous studies, aberrant methylation levels of ACE, ADD1, GCK, and 11β-HSD-2 were shown to correlate with the onset and development of EH [Friso et al, 2008;Riviere et al, 2011;Zhang et al, 2013;Rangel et al, 2014;Fan et al, 2015].…”
mentioning
confidence: 99%
“…In previous studies, aberrant methylation levels of ACE, ADD1, GCK, and 11β-HSD-2 were shown to correlate with the onset and development of EH [Friso et al, 2008;Riviere et al, 2011;Zhang et al, 2013;Rangel et al, 2014;Fan et al, 2015].…”
mentioning
confidence: 99%
“…Age-dependent gene methylation may also contribute to the phenotypic changes associated with skin aging (34). A previous study demonstrated that age-related DNA methylation affected the essential hypertension status (25). For the CDKN2A gene, older patients were more likely to be unmethylated in the present study, even when assessed independent of blood cholesterol and gender.…”
Section: Discussionmentioning
confidence: 39%
“…DNA extraction and quantification was performed as described previously (25). DNA samples were converted using an EZ DNA Methylation-Gold Kit (Zymo Research, Irvine, CA, USA), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, unmethylated cytosine residues of the target sequences of the candidate gene are first converted to thymine, using sodium bisulfite (EpiTect Bisulfite Kit, Qiagen, Hilden, Germany). The converted DNA is then amplified by polymerase chain reaction (PCR) using Mastercycler Nexus Gradient (Eppendorf, Hamburg, Germany), followed by “sequencing by synthesis” of the target (PyroMark Gold Q96, Qiagen) [21, 22]. The PCR reaction mixture consisted of 12  μ L ZymoTaq™ Premix (Zymo Research Corporation, Irvine, CA, USA), 8  μ L DNase/RNase-free water, 2  μ L converted DNA, and 1.5  μ L of each of the forward and reverse primers.…”
Section: Methodsmentioning
confidence: 99%